Hubungan tipe kepribadian OCEAN dan brand trust pada konsumen maskapai penerbangan low cost carrier - Octavianty, Octavianty; Jatmika, Devi (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2015)
The need of air transportation is increasing day by day. In order to satisfy this need, airline industries build low cost carrier airlines concept. However, low cost carrier concept may have some risk factors, especially the safety concern of passengers that should be the main priority of the aviation industries. This study aims to determine the relationship between OCEAN personality type and brand trust of AirAsia’s consumers. Quantitative research method was conducted in this research. The number of sample was 266 users of low cost carrier airline. Sampling technique used was accidental sampling. Data were collected and were statistically analyzed by using Spearman correlation technique. The results in this study indicate that there is a positive and significant correlation between personality type of Extraversion (r= 0.155; p< .05), conscientiousness(r= 0.216; p< .05), agreeableness(r = 0.254; p< .05), openess to experience (r= 0.613; p< .05) towards the brand trust. Moreover, there is significantand negative correlation between neuroticsm and brand trust(r= -0.268; p< .05).The descriptiveanalysis of brand trust revealed that consumers tend to have low trust to the low cost carrier airline.